HLA antigens and other risk factors in the development of retinopathy in type 1 diabetes. - Gray, R S (1982)
Factors possibly influencing the development of diabetic retinopathy were studied in 112 randomly selected type 1 diabetics having no or minimal retinopathy (group A) and in 82 type 1 diabetics with known severe diabetic retinopathy. The latter comprised those with severe background retinopathy (group B, n = 17) and those having proliferative retinopathy without (group C, n = 38) and with group D, n = 27) diabetic nephropathy. Nonretinopaths (group A) were of similar sex ratio, body weight, and age at diagnosis of diabetes but had been diabetic longer (p less than 0.001) and were thus older (p less than 0.001) than retinopaths (groups B-D). The distribution of HLA antigens of the A, B, and C loci was similar in nonretinopaths and retinopaths with the exception that HLA B7 showed a reduced (p less than 0.05) prevalence in the retinopaths (6% versus 17%) and was singularly underrepresented in group D, where no patients had this antigen. Mean postprandial plasma glucose and HbA1 concentrations were higher (p less than 0.01 and p less than 0.001) and cigarette smoking was more prevalent (p less than 0.01) in the retinopathy groups B-D than in group A. Systolic and diastolic blood pressures were similar in groups A-C, with higher (p less than 0.001) values only in group D. There was no association between insulin antibody binding in the serum or measurable plasma C-peptide immunoreactivity and retinopathy status. The risk of development of diabetic retinopathy in type 1 diabetes may be related to HLA-associated genetic factors and to cigarette smoking.